Three Phase Motor Speed Monitoring and Control System Using Raspberry Pi and Node RED in Molding Production at PT XYZ - Muhammad Nashruddin Alie; Denny Irawan (G-Tech: Jurnal Teknologi Terapan, 2025)
PT XYZ is a company that produces the largest automotive tools in Gresik. In producing the tool, a molding process is needed as a mold maker. In the molding process at PT XYZ, furan resin is used as a bonding agent and mixed with a catalyst in the appropriate proportion to produce a sand mold. Three-phase motor speed control in the molding process is very much needed so that the production process reaches maximum targets. The use of VFD in motor speed control can facilitate operators in the process of mixing materials for molding. Raspberry Pi combined with Node RED is an alternative as a cheap and efficient 3-phase motor speed monitoring and control system. The speed control of 3 phase motors on VFD can be done using Raspberry Pi with the help of Node RED as a communication bridge with VFD with Modbus protocol. The speed of 3 phase motors on VFD has an error percentage of 1.362% when compared to the UNI-T 373 tool. So that the monitoring and control system of 3 phase motors using Raspberry Pi and Node RED in molding production at PT XYZ is in accordance with the researcher's expectations and the system that has been designed can be implemented at PT XYZ.